The Promise and Perils of Direct Democracy: An Introduction - Donovan, Todd (2019)
Direct democracy promises politics that improve links between citizens and their representatives, and satisfies popular demand for increased engagement. In practice it may fall well short, given limited citizen capacity, poor information from campaigns, and ill-designed processes. The articles here represent the opportunities that direct democracy offers for the study of these promises and perils.